Hubungan Dukungan Keluarga Terhadap Kualitas Hidup Lansia Penderita Diabetes Melitus di Wilayah Kerja Puskesmas Cilandak Jakarta Selatan - Shinta Hidayati; Rima Berlian Putri (PT. Hasba Edukasi Mandiri, 2025)
Family support is an attitude and action of acceptance towards family members in the form of informational support, assessment support, instrumental support and emotional support. The good quality of life of elderly people with Diabetes Mellitus can be caused by family support factors. The aim of this research is to determine the relationship between family support and the quality of life of elderly people suffering from diabetes mellitus in the Cilandak Community Health Center working area. This research uses a correlational analytical design with a cross sectional approach. The sampling technique used purposive sampling technique, the sample in this study was 78 respondents. Data collection used the Family Support Questionnaire and the Diabetes Quality of Life (DQOL) Questionnaire. The research results were obtained from 78 respondents, as many as 54 respondents (69.2%) were female, as many as 68 respondents (87.2%) were aged 60-74 years, as many as 40 respondents (51.3%) had at least a high school education, as many as 76 respondents (97.4%) did not working, as many as 53 respondents (67.95%) had a history of Diabetes Mellitus > 5 years, as many as 41 respondents (52.6%) had poor family support and as many as 44 respondents (56.4%) had poor quality of life. The results of the Chie Square Statistical Test show that the P-Value = 0.034, where p < 0.05. The conclusion of this research is that there is a relationship between family support and the quality of life of elderly people suffering from diabetes mellitus in the working area of ​​the Cilandak Health Center, South Jakarta. Nurses are expected to be able to involve families directly in improving the quality of life of elderly people suffering from Diabetes Mellitus at home and in community health centers.